KONFLIK TOKOH UTAMA DALAM CERPEN ANAK MAJALAH BOBO 2017 DAN IMPLEMENTASINYA DALAM PEMBELAJARAN SASTRA DI SLTP - Fadhilatun Hayatunnufus (Kantor Bahasa Lampung, 2018)
AbstractThis study aims to describe the conflict of the main character in the children's short story 2017 Bobo magazine and its implementation in literature learning in primary schools. This research includes literature research that uses data in the form of narration, description, and dialogue in the form of written data on children's short stories in Bobo magazine with the number ten short stories. Data collection by documenting, literature study, reading and recording. As for data processing, the content analysis method is used. Through this research, it was concluded that the conflict of the main character that occurred in the children's short story included internal and external conflicts. Internal conflict, namely the conflict between the main character and himself. External conflict, namely the conflict between the main character and other people and nature. conflicts in children's stories Bobo magazine is a simple conflict that is easily resolved by children. The results of this analysis can be implemented for literary teaching in the junior high school class XI odd semester. Grade XI junior high school students are expected to understand conflicts and solutions in children's short stories.AbstrakPenelitian ini bertujuan untuk mendeskripsikan konflik tokoh utama dalam cerpen anak majalah Bobo 2017 dan implementasinya dalam pembelajaran sastra di sekolah dasar. Penelitian ini termasuk penelitian kepustakaan yang menggunakan data berupa narasi, deskripsi, dan dialog berupa data tertulis pada cerpen anak-anak dalam majalah Bobo dengan jumlah sepuluh judul cerpen. Pengumpulan data dengan cara mendokumentasi, studi pustaka, membaca, dan mencatat. Adapun untuk mengolah data digunakan metode analisis isi. Melalui penelitian ini, diperoleh simpulan bahwa konflik tokoh utama yang terjadi dalam cerpen anak tersebut, meliputi konflik internal dan eksternal. Konflik internal, yaitu konflik tokoh utama dengan dirinya sendiri. Konflik eksternal, yaitu konflik tokoh utama dengan orang lain dan alam. konflik-konflik dalam cerpen anak majalah Bobo merupakan konflik sederhana yang mudah diselesaikan oleh anak-anak. Hasil analisis ini dapat diimplementasikan untuk pengajaran sastra di SLTP kelas XI Semester ganjil. Siswa SLTP kelas XI diharapkan dapat memahami konflik beserta solusi dalam cerpen anak-anak.